China's rise: Challenging the North-South technology transfer paradigm for climate change mitigation and low carbon energy. (February 2018) - Urban, Frauke
Abstract: Historically, technology transfer from the global North to China played a large role in renewable energy pathways in China, particularly for wind energy, partly also for solar energy. Yet, the rise of China and other emerging economies means a shift away from a reliance on technology transfer and production capabilities to strengthening indigenous innovation capabilities. Drawing on evidence from the hydropower, solar and wind energy industry in China, the paper introduces the concept of 'geographies of technology transfer and cooperation' and challenges the North-South technology transfer and cooperation paradigm for low carbon innovation and climate change mitigation. The empirical evidence shows that for low carbon innovation, the conception that China is lacking behind in innovation capabilities is partly outdated. Instead, there is an increase in indigenous innovation capabilities, resulting in South-South technology transfer and cooperation as well as elements of 'reverse' South-North technology cooperation. Highlights: Historically China relied on technology transfer for low carbon technology (LCT). Today China's rise means a shift from technology transfer to indigenous innovation. Empirical research on the hydropower, solar and wind energy industry in China. Findings challenge the North-South technology transfer and cooperation paradigm. Rise of South-South and South-North technology transfer and cooperation for LCT.